Comparison of different QT interval correction methods for heart rate and QT beat‐to‐beat method in a thorough QT study of triple monoamine reuptake inhibitor BMS‐820836. (9th June 2015) - Zheng, Ming; Burt, David; Chan, Wai; Hawthorne, Dara; Gasior, Maciej; Bhagwagar, Zubin; Keswani, Sanjay; AbuTarif, Malaz; Bertz, Richard
Abstract As BMS‐820836 causes dose‐dependent heart rate increases, QTcI, QTcF, QTcB, and QT beat‐to‐beat methods were compared in this thorough QT study in healthy subjects. Two parallel groups of subjects (n = 60 per group) received 2 mg (maximum therapeutic) or 4 mg (supratherapeutic) of BMS‐820836 once daily for 14 days with uptitration. Another 60 subjects received encapsulated moxifloxacin (400 mg) or matching placebo in a nested‐crossover study design. Compared with QTcF and QTcB, baseline QTcI had the smallest and near‐zero Pearson correlation coefficient with heart rate (0.0938), which supported the choice of QTcI as the primary electrocardiographic end point. BMS‐820836 was not associated with prolongation of the QT interval at the doses tested; however, ΔΔQTbtb showed the smallest deviation from 0 milliseconds compared with ΔΔQTcI and ΔΔQTcF. The ΔΔQTbtb results appeared to be more consistent with the very low likelihood of any effect on the QT interval by BMS‐820836 based on the wide margin (>400×) of the in vitro hERG IC50 and free plasma concentration. Further, this is the first published study that used the nested‐crossover design and QTbtb analysis in a thorough QT study. Assay sensitivity was confirmed with encapsulated moxifloxacin.